State of the art of the literature on definitions of self-criticism: a meta-review - Zaccari, Vittoria; Mancini, Francesco; Rogier, Guyonne (Frontiers in Psychiatry, 2024)
Background Several authors have developed important theoretical models on an important transdiagnostic factor in psychopathology: self-criticism (SC). Currently, there are substantial variations in the theoretical definition of SC. The lack of awareness of similarities and differences between models may in turn impact the comparison between empirical results, limiting their clinical implications. Purpose The purpose of this study was to identify current trends in the field of SC and to explore whether these were approached and shaped by different conceptualizations of SC. Methods Core components of the most influential models of SC were identified. A meta-review was conducted searching for systematic reviews and/or meta-analyses in the following databases: PsycINFO, PsycARTICLES, MEDLINE, Scopus, Web of Science, and PubMed (all years up to 28 April 2023). Results Contributions were heterogeneous with respect to the definition of SC and the theoretical framework. Almost all systematic reviews poorly addressed the multidimensionality of SC. In addition, discrepancies between the definitions of SC provided and their operationalizations emerged. Conclusions The lack of dialogue between the different theoretical perspectives emerged from key contributions in the field of SC. Potential research questions to answer to stimulate this dialogue are proposed.